RELEVANSI PENDIDIKAN ISLAM DENGAN PEMBENTUKAN KARAKTER BANGSA - Hendrizal; Wirma Datil Husna; Nurtika Syafitri; Dewi Oktavia; Titit putriani; Masidah Daulay (EDU RESEARCH, 2024)
Islamic Religious Education is one of the main components in the formation of the nation's character and personality. In this context, Islamic religious education does not only focus on the cognitive aspect, but also on the formation of noble morals that are the basis for daily life. This education plays a role in developing the moral and spiritual potential of individuals, as well as forming a wise mindset in facing the challenges of the times. The research methodology used in this study is the literature study method, in which the author collects, analyzes, and synthesizes relevant information from various written sources such as books, scientific journals, and articles related to Islamic education with the formation of the nation's character. The result of this research is that Islamic Education not only teaches religious science, but also focuses on internalizing the fundamental values of Islam in daily life. This education aims to shape character through the instillation of values such as honesty, justice, and responsibility, which must be integrated in various disciplines and behaviors. Character education is expected to form individuals with noble morals and good morals, which is reflected in social, spiritual, and ecological interactions. In the context of the nation, Islamic education plays an important role in strengthening the nation's character by introducing noble moral values, which will create peace and happiness in the community. Keywords: Islamic Education, Character and Nation